The spesies diversity of arthropods in surjan and conventional farming systems in the Special Region of Yogyakarta - Wagiyana, Wagiyana; Alfarisy, Fariz Kustiawan; Suharto, Suharto; Habriantono, Bakhroini; Khozin, Mohammad Nur; Suandana, Febery Hery (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
An ecosystem is the relationship between insects and the environment in carrying out life processes. The majority of insects are herbivores, and plants serve as their main hosts. Plants also secrete hormone compounds that are favored by arthropods as both a food source and a host for survive. Based on their nature, arthropods are divided into pests and natural enemies. The surjan system is one of the agroecosystem modifications for sustainable agriculture. The study aimed to assess arthropod spesies diversity in different cropping systems. Monitoring was conducted on surjan and conventional land, using several types of traps, including pitfall traps, yellow traps, and pheromone traps. The diversity of arthropods in an ecosystem serves as an indicator of environmental health. This research provides recommendation for managing arthropods, whether as pests or natural enemies. The highest diversity index value was found in the conventional system, with the Shannon_H’ value of of 1.57 for trapping 1, 1.27 for trapping 2, 2.06 for trapping 3, and 1.20 for trapping 4. The species diversity (H’ > 1) value was classified in the medium category. The results of morphological identification revealed two species with the highest abundance: Bactrocera sp. and Atherigona sp. The effectiveness of yellow traps was higher compared to other types of trap, capturing a total of 280 species of pests.